Analysis of Hate Speech in Responses to Two Hausa Online Media Outlets on the Spread of the COVID-19 Pandemic - Gbeyonron, Clifford Irikefe (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2024)
Effective communication through the medium of indigenous languages serves as an invaluable instrument that facilitates every language’s right to information during pandemics. Different online media outlets used Nigerian languages to disseminate information that could enhance the success of public health measures targeted at mitigating the impact of COVID-19. However, not all of the audience absorbed the messages positively. This study attempts to analyze the use of hate speech in the comments of readers of Hausa online news items on Legit Hausa and BBC Hausa that responded to news items on COVID-19. To achieve this, the readers' comments were purposively sampled and analyzed based on the pragmatic principles of politeness and peaceful communication. In addition, systemic functional grammar was used to explicate the grammatical features of the analyzed linguistic elements of the comments written in Hausa. It was found that the comments were not only replete with inflammatory language – stripping the users of the status of communicative humanizer – inimical to preventive measures against COVID-19 but also capable of widening the opinion divide. Furthermore, most comments analyzed flout the principles of Hausa spelling and sentence construction. The study thus recommends that linguistic activists should consistently advocate for the use of Nigerian languages that conform to linguistic norms and the principles of peaceful communication that would curtail misinformation and division in the course of pandemic control.